A Review of the Energy Performance Gap and Its Underlying Causes in Non-Domestic Buildings - van Dronkelaar, Chris; Dowson, Mark; Burman, E.; Spataru, Catalina; Mumovic, Dejan (Frontiers in Mechanical Engineering, 2016)
This paper reviews the discrepancy between predicted and measured energy use in non-domestic buildings in a UK context with outlook to global studies. It explains differences between energy performance quantification and classifies this energy performance gap as a difference between compliance or performance modelling with measured energy use. Literary sources are reviewed in order to signify the magnitude between predicted and measured energy use, which is found to deviate by +34% with a standard deviation of 55% based on 62 buildings. It proceeds in describing the underlying causes for the performance gap, existent in all stages of the building life cycle, and identifies the dominant factors to be related to specification uncertainty in modelling, occupant behaviour and poor operational practices having an estimated effect of 20-60%, 10-80% and 15-80% on energy use respectively. Other factors that have a high impact are related to establishing the energy performance target, impact of early design decisions, heuristic uncertainty in modelling and occupant behaviour. Finally action measures and feedback processes in order to reduce the performance gap are discussed, indicating the need for energy in-use legislation, insight into design stage models, accessible energy data and expansion of research efforts towards building performance in-use in relation to predicted performance